2009
DOI: 10.1038/msb.2009.49
|View full text |Cite
|
Sign up to set email alerts
|

Cell–cell interaction networks regulate blood stem and progenitor cell fate

Abstract: Communication networks between cells and tissues are necessary for homeostasis in multicellular organisms. Intercellular (between cell) communication networks are particularly relevant in stem cell biology, as stem cell fate decisions (self-renewal, proliferation, lineage specification) are tightly regulated based on physiological demand. We have developed a novel mathematical model of blood stem cell development incorporating cell-level kinetic parameters as functions of secreted molecule-mediated intercellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
121
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 62 publications
1
121
0
1
Order By: Relevance
“…Recent studies have identified a variety of negative-feedback strategies for achieving robust control of tissue size and cell number (Shraiman, 2005;Kirouac et al, 2009;Lander et al, 2009). The olfactory epithelium (OE) of the mouse has been a particularly useful model system in this regard .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified a variety of negative-feedback strategies for achieving robust control of tissue size and cell number (Shraiman, 2005;Kirouac et al, 2009;Lander et al, 2009). The olfactory epithelium (OE) of the mouse has been a particularly useful model system in this regard .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, two emulsions with droplets 20 containing single cells could pass through a sorter and then be reinjected and coalesced in our device for the study of cell-cell interactions. 17 We plan to use the method to create droplets with controlled numbers of various kinds of Brownian particles to study colloidal self-assembly. …”
Section: Resultsmentioning
confidence: 99%
“…According to the authors' statement [8] this sloppiness is a potential explanation to "[...] the difficulty of extracting precise parameter estimates from collective fits, even from comprehensive data." Nowadays, the term sloppiness is often found in the literature and sometimes erroneously used for concluding that parameters cannot be estimated and identified and thereby is sometimes utilized as an excuse that the parameter estimation behaves poorly [27][28][29].…”
Section: Sloppinessmentioning
confidence: 99%